Mucosal immunity in COVID-19: a comprehensive review - Alqahtani, Saeed Awad M. (Frontiers in Immunology, 2024)
Mucosal immunity plays a crucial role in defending against coronaviruses, particularly at respiratory sites, serving as the first line of defense against viral invasion and replication.Coronaviruses have developed various immune evasion strategies at the mucosal immune system, hindering the recognition of infected cells and evading antibody responses. Understanding the immune mechanisms and responses is crucial for developing effective vaccines and therapeutics against coronaviruses. The role of mucosal immunity in COVID-19 is significant, influencing both local and systemic immune responses to the virus. Although most clinical studies focus on antibodies and cellular immunity in peripheral blood, mucosal immune responses in the respiratory tract play a key role in the early restriction of viral replication and the clearance of SARS-CoV-2.Identification of mucosal biomarkers associated with viral clearance will allow monitoring of infection-induced immunity. Mucosally delivered vaccines and those under clinical trials are being compared and contrasted to understand their effectiveness in inducing mucosal immunity against coronaviruses. A greater understanding of lung tissue-based immunity may lead to improved diagnostic and prognostic procedures and novel treatment strategies aimed at reducing the disease burden of community-acquired pneumonia, avoiding the systemic manifestations of infection and excess morbidity and mortality. This comprehensive review article outlines the current evidence about the role of mucosal immune responses in the clearance of SARS-CoV-2 infection, as well as potential mucosal mechanisms of protection against (re-)infection. It also proposes that there is a significant role for mucosal immunity and for secretory as well as circulating IgA antibodies in COVID-19, and that it is important to elucidate this in order to comprehend especially the asymptomatic and mild states of the infection, which appear to account for the majority of cases.Moreover, it is possible that mucosal immunity can be exploited for beneficial diagnostic, therapeutic, or prophylactic purposes. The findings from recent studies on mucosal immunity in COVID-19 can be used to develop effective vaccines and treatments that can effectively target both mucosal and systemic immune responses.